2018
DOI: 10.3390/md16070221
|View full text |Cite
|
Sign up to set email alerts
|

Seaweed Extract (Stella Maris®) Activates Innate Immune Responses in Arabidopsis thaliana and Protects Host against Bacterial Pathogens

Abstract: Insects and pathogenic infections (bacteria, viruses and fungi) cause huge losses in agriculturally important crops yearly. Due to the rise in pesticide and antibiotic resistance, our crops and livestock are increasingly at risk. There is a rising demand for environmentally friendly solutions to prevent crop decreases. Components of Ascophyllum nodosum seaweed extracts were recently found to boost plant immunity. The stimulatory activities of the A. nodosum marine alga-derived extract (Stella Maris®) were inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 48 publications
1
19
1
Order By: Relevance
“…The induction of hydrogen peroxide was found only in those roots treated with the three seaweed extracts individually and infected with P. cinnamomi. This result is somewhat different to that of a previous study (Cook et al, 2018) that showed the induction of reactive oxygen species in seedlings treated only with an A. nodosum extract. This variation in results between the two studies may reflect differences in preparation of the extract and the treatment and analysis methods.…”
Section: Role Of Ros In Seaweed Induced Plant Defensecontrasting
confidence: 99%
See 1 more Smart Citation
“…The induction of hydrogen peroxide was found only in those roots treated with the three seaweed extracts individually and infected with P. cinnamomi. This result is somewhat different to that of a previous study (Cook et al, 2018) that showed the induction of reactive oxygen species in seedlings treated only with an A. nodosum extract. This variation in results between the two studies may reflect differences in preparation of the extract and the treatment and analysis methods.…”
Section: Role Of Ros In Seaweed Induced Plant Defensecontrasting
confidence: 99%
“…Other studies have shown similar upregulation of these genes at a single time point. For example, it had been shown earlier that the expression of the PR1 gene in A. thaliana was up-regulated at 24 h post-treatment with an A. nodosum-based extract (Cook et al, 2018;Shukla et al, 2019). Furthermore, carrot plants primed by A. nodosum-derived extracts induced the accumulation of transcripts of the same or similar genes (Jayaraj et al, 2008).…”
Section: Effect Of Seaweed Extracts On Key Regulatory Resistance-relamentioning
confidence: 94%
“…Another A. nodosum -derived extract (Stella Maris ® ) was reported to boost plant immunity by elevating the production of hydrogen peroxide, which ultimately led to an increase in the concentration of ROS. It was further shown that the expression of plant immune response genes WRKY30 , CYP71A12 , and PR-1 (genes that activate in early, mid, and late phases of immunity in the plant, respectively) was up-regulated (Cook et al, 2018). The priming of 3-week-old A. thaliana plants with 1 g/L of ANE (25 ml per plant through root drench) 2 days prior to inoculation protected against the necrotic pathogen, Sclerotinia sclerotiorum (Subramanian et al, 2011).…”
Section: Ane Improves Plant Defenses Against Various Pathogensmentioning
confidence: 99%
“…A. nodosum extracts prepared by Acadian Seaplants Limited, induced systemic defense responses against Pseudomonas syringae and S. sclerotiorum by inducing the expression of the genes involved in the JA-dependent pathway [ 145 ]. The pre-treatment of Stella Maris ® (Acadian Seaplants), a commercial extract prepared from A. nodosum, inhibited the growth of several bacterial pathogens in A. thaliana by inducing a strong oxidative burst of reactive oxygen species (ROS) [ 132 ]. In addition to this, Stella Maris ® , also induced the expression of cytochrome P450 family polypeptide ( CYP71A1 2), an antimicrobial phytoalexin known to damage the cell wall and disrupt the metabolism of bacterial pathogens [ 132 ].…”
Section: Seaweeds: Sources Of Extracts Used As Biostimulantsmentioning
confidence: 99%
“…The pre-treatment of Stella Maris ® (Acadian Seaplants), a commercial extract prepared from A. nodosum, inhibited the growth of several bacterial pathogens in A. thaliana by inducing a strong oxidative burst of reactive oxygen species (ROS) [ 132 ]. In addition to this, Stella Maris ® , also induced the expression of cytochrome P450 family polypeptide ( CYP71A1 2), an antimicrobial phytoalexin known to damage the cell wall and disrupt the metabolism of bacterial pathogens [ 132 ]. The expression of other defense-related genes, such as WRKY30 and PR1 , was also find higher in A. thaliana in response to a P. syringae infection [ 132 ].…”
Section: Seaweeds: Sources Of Extracts Used As Biostimulantsmentioning
confidence: 99%